Legal problems of the development of transport plants and their solution in Kazakhstan, developed countries and UNIDO - Sarsembayev, M.A. (Bulletin of the Karaganda University “Law Series”, 2021)
In the conditions of the fourth industrial revolution, modern science should look for answers to the challenges and problems that many countries, including Kazakhstan, are facing today. First of all, they need to be solved in key areas of the economy, which includes transport engineering as one of the leading branches of the national and world economy. This article is devoted to the consideration of the main trends and prospects for the development of national and international law of transport engineering and legal problems of its factories (concerns) in order to develop proposals so that this development becomes optimal, useful, mutually beneficial for states, including Kazakhstan, for the regions and the international community as a whole. Today in the field of transport engineering such an intensively functioning institution as UNIDO (United Nations Industrial Development Organization) is engaged in solving organizational and economic issues, problems of transport engineering from the point of view of both public international law and private international law. The article analyzes the internal laws of Kazakhstan and a number of developed countries, the set of norms of which forms the national, including the Kazakh, law of transport engineering.